In their Shoes: Empathy Through Information - Andries, Marianne; Bursztyn, Leonardo; Chaney, Thomas; Djourelova, Milena; Imas, Alex (Quarterly Journal of Economics, 2026)
Abstract We explore the mechanics of empathy. We show that information about an outgroup can activate and magnify empathy when presented in conjunction with an experience simulating their struggles. This response increases the willingness to help the struggling group. We provide evidence for this effect in an immersive virtual reality experiment where participants (“witnesses”) experience a simulation of the struggle of unauthorized migrants (“protagonists”), then replicate these results in a series of controlled lab experiments. We show that information enhances the witnesses’ empathetic response and drives them to engage in more prosocial behavior when it increases their perceived interpersonal similarity, or relatability to the protagonist — an effect we trace to attention: eye-tracking data reveals that information provision concentrates witnesses’ gaze on the struggles of the protagonist instead of searching through peripheral elements of the scene. Conversely, only information packages that strengthen perceived relatability — an effect that can vary across subgroups with heterogeneous attributes — magnify empathy. Together, our evidence suggests that the ability to put oneself in the shoes of another person or group can be enhanced by activating empathy through simple, targeted, information provision.